Responsibilities of the Kajen Pekalongan Regional General Hospital on the Loss of Septum in Infants Due to Safety Incidents Installation of Continuous Positive Airway Pressure. Case Study at Kajen Hospital - Yoga Dewa Brahma; Tjahjono Kuntjoro; Valentinus Suroto (Universitas Katolik Soegijapranata Semarang, 2021)
Abstract: Health World Has Been Rapidly Developing Which Includes Health Services And Health Care Facilities. This Is Not Directly Proportional To The Existing Legislations Regulating Health Services Affairs So That It Will Possibly Create Legal Problems In Health Services Which Involve Health Workers And Health Service Facilities. One Of The Problems Happened At Regional General Hospital (RSUD) Of Kajen. The Hospital Was Suspected That The Health Workers Were Negligent In Providing Health Services, Particularly Relating With The Installation Of Continuous Positive Airway Pressure (CPAP) Which Resulted in The Baby Losing The Septum. As The Consequence, The Baby Should Be Sent To A Hospital Having Plastic Surgery Facilities To Repair The Septal DamageThe Objective Of This Study Was To Determine The Implementation Of The Referral System And Hospital Legal Responsibility Against Baby’s Septum Loss Due To The Incident Of CPAP Installation Safety At RSUD Kajen. The Study Used A Socio-Legal Approach Having A Descriptive Analytic Specification. The Data Used Were Primary And Secondary Meanwhile The Data Gathering Techniques Were By Interviews With Resource Persons And Library Studies On Primary, Secondary, And Tertiary Legal Materials Beside Some Other Relevant Written Materials. The Data Were Then Qualitatively Analyzed.The Results Of This Study Showed That The Referral System In The Case Of Baby’s Septal Loss Due To The Incident Of CPAP Installation Safety At RSUD Kajen Was Considered Inappropriate. Based On Article 4 Of The Minister Of Health No. 1 Of 2012 Concerning Individual Health Service Referral Systems Was Deemed Inappropriate, Kajen General Hospital Should Refer To Patients' Medical Needs. The Implementation Of Hospital Legal Liability, In This Case, Is Based On Article 1365 Of The Civil Code, Article 1367 Of The Civil Code And Article 46 Of Law Nr. 44 Of 2009 Concerning Hospitals, That There Has Been An Unlawful Act, Therefore The Kajen Regional Hospital Conducts Accountability. Abstrak: Perkembangan dunia kesehatan sangatlah pesat dari pelayanan kesehatan maupun fasilitas pelayanan kesehatan. Hal ini tidak berbanding lurus dengan regulasi yang mengatur hubungan mengenai pelayanan kesehatan sehingga tidak menutup kemungkinan akan menimbulkan permasalahan hukum dalam pelayanan kesehatan terhadap tenaga kesehatan dan fasilitas pelayanan kesehatan. Seperti kasus yang terjadi di Rumah RSUD Kajen diduga terjadi kelalaian tenaga medis dalam memberikan pelayanan kesehatan, yaitu dalam pemasangan Continous Positive Airway Pressure (CPAP) yang mengakibatkan bayi tersebut kehilangan septum sehingga harus menjalani perawatan ke rumah sakit yang mempunyai fasilitas bedah plastik untuk memperbaiki kerusakan septum tersebut. Penelitian ini bertujuan untuk mengetahui pelaksanaan sistem rujukan dan tanggung jawab hukum rumah sakit atas hilangnya septum pada bayi akibat insiden keselamatan pemasangan CPAP di RSUD Kajen.Penelitian ini merupakan penelitian yuridis sosiologis dengan spesifikasi deskriptif analitik. Penelitian ini menggunakan data primer dan sekunder. Adapun tekhnik pengumpulan data yang digunakan adalah wawancara kepada narasumber serta studi kepustakaan yang dilakukan dengan mempelajari bahan hukum primer, sekunder dan tersier. Analisis data dilakukan secara kualitatif.Hasil penelitian menunjukkan bahwa sistem rujukan pada kasus hilangnya septum pada bayi akibat insiden keselamatan pemasangan CPAP di RSUD Kajen berdasarkan Pasal 4 Permenkes Nomor 1 Tahun 2012 tentang Sistem Rujukan Pelayanan Kesehatan Perorangan dinilai tidak tepat, seharusnya RSUD Kajen melakukan rujukan berdasarkan kebutuhan medis pasien. Pelaksanaan pertanggungjawaban hukum rumah sakit dalam kasus ini berdasarkan Pasal 1365 KUH Perdata, Pasal 1367 KUH Perdata maupun Pasal 46 Undang-Undang Nomor 44 Tahun 2009 tentang Rumah Sakit, bahwa telah terjadi perbuatan melawan hukum, maka dari itu RSUD Kajen melakukan pertanggungjawaban.